El rol de los juegos en los tres niveles de educación básica del colegio Melitón Carvajal durante el año 2019 - Campos Vargas, Gabriela (2020)
The purpose of this research is to expose the role played by games and its importance in teaching as a tool that encourages learning through its motivational, cognitive and creative load, for that reason it must be implemented in the three levels of basic education. It is not only about providing knowledge-based education and standardized tests, but it is also important to emphasize the skills and emotions of each student. To carry out this research, the Melitón Carvajal national school has been taken as a case study, they have worked with in-depth interviews to know the perception of a sample made up of the deputy director and teachers of the school that provides clear ideas about what the position is that the actors directly involved with education give to games in the lives of students; Likewise, specialists on the subject have been used, which has allowed us to have an academic perspective that supports the importance of the role of games in education. One of the main conclusions that was obtained from this research is that there is still a limited acceptance of the game in education, they see it more as a tool loaded with motivational incentives, but not as a tool in charge of educating.